Modern strategies of platinum resistance overcoming in patients with the serous ovarian cancer - Rybin, Andriy (Journal of Education, Health and Sport, 2018)
The study was aimed to determine the platinum-resistance biomarkers in patients with ovarian cancer. The expression of ABCA1 is higher in platinum-resistant cases of ovarian cancer. The most pronounced relationship exists between the values of survivin expression, local activity of nitric oxide, the expression of glutathione dependent enzymes, the content of catecholamines in erythrocytes, and the expression of ABCA1 transporter